Case report: A relevant misdiagnosis: Photosensitive epilepsy mimicking a blinking tic - Burlo, Francesca; Barbi, Egidio; Carrozzi, Marco; Zanus, Caterina (Frontiers in Pediatrics, 2022)
Blinking in children is most frequently a functional and transient symptom. Nonetheless, sometimes it is the first clinical manifestation of a neurological disorder. The differential diagnosis between voluntary actions, tics and other neurological disorders among which seizures may be challenging and misdiagnosis is common. A six-year-old girl in good health was admitted for a recent history of bilateral eye blinking. Blinking did not interfere with the girl’s activities. The patients reported that blinking seemed to be triggered by sunlight exposure and that girl sometimes seemed to be attracted by the sunlight. Ophthalmological diseases had been already excluded. The girl was addressed to our hospital for neurological consultation, as tic disease was considered the most probable hypothesis. Neurological examination was negative. In the field of differential diagnosis of photosensitive abnormal eyelid movements, the hypothesis of seizures was explored and further investigated with a video-EEG recording with light stimulation. This exam demonstrated a photoparoxysmal response (PPR) to intermittent photic stimulation with appearance on EEG of bilateral spike and polyspike waves associated with eyelid jerks. This girl suffers from generalized epilepsy with photosensitivity. Photosensitivity is a common feature of many epilepsy syndromes, mainly occurring in children and adolescents. To control the seizures, it is essential to avoid the triggering stimulus, by wearing specific glasses. Additional antiseizures treatment is often necessary, at first with valproate and levetiracetam, and ethosuximide, lamotrigine, and benzodiazepines as the second choice. Overlapping phenomenology of seizures and movement disorders is well known in paediatric clinical practice. Moreover, epilepsy and movement disorder may coexist, mainly in children. Seizures with semeiology limited to eye motor manifestations may mimic functional blinking, tics, and other motor events frequently observed in childhood. Differentiating seizures from other non-epileptic paroxysmal movements may be challenging and specialist evaluation is needed for proper treatment and prognostic counselling.